CRISPR/Cas9-Based Deletion of SpvB Gene From Salmonella gallinarum Leads to Loss of Virulence in Chicken - Basit, Abdul; Tahir, Hamza; Haider, Zulquernain; Tariq, Hafsa; Ullah, Asim; Rehman, Shafiq Ur (Frontiers in Bioengineering and Biotechnology, 2022)
Salmonella Gallinarum causing fowl typhoid in poultry led huge economic loss to poultry industry. The large virulence plasmid of S. Gallinarum has been associated with various systemic infections in poultry. Five genes spanning region (spvRABCD) of 6.2 kb on the large plasmid mainly confer virulence to bacteria. However, the exact role of these genes in virulence has not been elucidated yet. SpvB exhibits a delayed cell death through preventing actins polymerization followed by apoptosis during intracellular infection. The specific role of SpvB in causing disease is not known yet. In the current study, SpvB gene was deleted through engineered CRISPR/Cas9 method from large virulent plasmid of locally isolated S. Gallinarum strain (SG18). Homology directed repair method was used for complete deletion of SpvB gene using modified pCas9 plasmid. The SpvB deleted S. Gallinarum strain (ΔSpvB_SG18) when tested for their virulence in broiler chicken showed no mortality and disease signs. In addition, the avirulent strain does not affect the bird’s weight and was rapidly cleared from liver after infection. However, it cleared from intestine after 4-5 days, which suggests that the ΔSpvB_SG18 strain is unable to invade from intestine to liver. This is the first study to report a complete gene deletion from S. Gallinarum virulent plasmid and their effect. This method will be useful for deletion of virulent genes from S. Gallinarum, to study their role in pathogenesis and to prepare an effective vaccine strain for controlling fowl typhoid in poultry.